Matilda - Dahl, Roald; Blake, Quentin (New York, N.Y. Viking Kestrel, 1988)
Matilda applies her untapped mental powers to rid the school of the evil, child-hating headmistress, Miss Trunchbull, and restore her nice teacher, Miss Honey, to financial security.
Keywords: Schools -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Girls -- Juvenile fiction